Strategi pengembangan profesionalisme penyuluh dalam peningkatan mutu penyuluhan pertanian - Oke Andikarya (University of Insan Cendekia Mandiri, 2021)
Agricultural extension is less clear, so it needs to be addressed, by developing professionalism of extension workers in improving the quality of agricultural extension. How is the implementation of strategic management in improving the quality of agricultural extension. The research objectives were to identify and analyze: 1. SWOT internal environment (strengths and weaknesses) and external environment (opportunities and challenges / threats); 2. Strategic formulation; 3. Strategic implementation; 4. Management of supervision and evaluation of agricultural extension professionalism; 5. Strategic steps to overcome problems and weaknesses. The research method uses a qualitative approach. Research location: BP3K Sukalarang and Sukabumi Subdistricts, West Java. The underlying theory is educational management, strategic management, human resource management, agricultural management and extension, quality theory and culture. The research findings are: 1. Not all BP3K heads have analyzed and combined their strengths, weaknesses, opportunities and challenges into the conclusion of strategic assumptions in the preparation of strategic plans; 2. Strategic formulation has not been based on strategic assumptions by maximizing strengths and minimizing weaknesses by taking advantage of opportunities in facing challenges. Vision, mission, strategic objectives and policies for professional development of extension workers are integrated in RENSTRA BP4K; 3. Strategic implementation includes programs, budgets and implementation procedures contained in the BP3K Annual Work Plan Program with a nominal BP3K Budget Work Plan, the agricultural extension professionalism development program has not been specifically regulated; 4. Supervision and evaluation of the professionalism of agricultural extension workers have not collaborated between the Head of BP3K and the district agricultural extension coordinator. The head of BP3K has not reported the results of the detailed and periodic professionalism assessment of agricultural extension agents to the district agricultural extension coordinator; 5. Strategies to overcome problems in an anticipatory manner through fostering motivation to all agricultural extension workers. Research recommendations: it is recommended that BP3K heads maximize strengths, minimize weaknesses, take advantage of opportunities to overcome challenges. Strategic assumptions are the basis for formulating vision, mission, goals, strategies and policies so that the professionalism of agricultural extension workers can develop to improve the quality of agricultural extension.